Implementation on ICT Knowledge Development in Healthcare - Vimala, Govindaraju; Siti Zobidah, Omar (2016)
Information and Communication Technology or ICT actually refers to a broad spectrum of technologies that allow users to get, produce, and share ideas and resources (Paul, 2003). ICT involves of unlimited e-mail, decision support system, and health information system. This kind of ICT based facility is able to assist medical professionals in medical coding, medical billing, registration, accounting, communicating among others. According to Ahmad (2008), in Malaysia, there are increasing demands for health tourism, so the hospitals need to upgrade their healthcare services to meet international standards; the increasing pressure for government to upgrade the healthcare industry and today’s tech-savvy consumers demanding better healthcare and customer services are some of the driving factors in adopting automation in the healthcare industry